2016 SIIL Annual Meeting - Appropriate Scale Mechanization Consortium - Hansen, Alan (Kansas State University, 2016)
Dr. Alan Hansen, Director of the Appropriate Scale Mechanization Consortium of the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification (SIIL), presents his project to the SIIL community. Filmed in January 2016.